2018
DOI: 10.1139/cjpp-2017-0559
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects ofN-acetylcysteine on hepatic oxidative stress in streptozotocin-induced diabetic rats

Abstract: Diabetes is one of the leading diseases worldwide and, thus, finding new therapeutic alternatives is essential. The development of non-alcoholic fatty liver disease is a notable diabetic complication. Therefore, antioxidant therapy became a leading topic in the world of diabetes research. The objective of this present study was to evaluate the effects of antioxidant N-acetylcysteine (NAC) administration on serum biochemical parameters and oxidative stress parameters in hepatic tissue of the diabetic rats. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…After reviewing the titles and abstracts in the records, we excluded the literature that is not related to the efficacy of NAC in NAFLD, systematic reviews, clinical trials, conference abstracts, books, and theses. Then, 34 full-text articles were carefully assessed for eligibility, and a total of 13 studies were finally involved in the meta-analysis ( Figure 1 ) ( Rosa et al, 2018 ; Shi et al, 2018 ; Wang et al, 2018 ; Chaves Cayuela et al, 2020 ; Ma et al, 2020 ; Tsai et al, 2020 ; Hang et al, 2021 ; Quesada-Vazquez et al, 2021 ; Yang et al, 2021 ; Ding et al, 2022 ; Lee et al, 2022 ; Liggett et al, 2022 ; Yang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the titles and abstracts in the records, we excluded the literature that is not related to the efficacy of NAC in NAFLD, systematic reviews, clinical trials, conference abstracts, books, and theses. Then, 34 full-text articles were carefully assessed for eligibility, and a total of 13 studies were finally involved in the meta-analysis ( Figure 1 ) ( Rosa et al, 2018 ; Shi et al, 2018 ; Wang et al, 2018 ; Chaves Cayuela et al, 2020 ; Ma et al, 2020 ; Tsai et al, 2020 ; Hang et al, 2021 ; Quesada-Vazquez et al, 2021 ; Yang et al, 2021 ; Ding et al, 2022 ; Lee et al, 2022 ; Liggett et al, 2022 ; Yang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, to fill the gap between preclinical and clinical studies, we performed a systematic review and meta-analysis for the efficacy of NAC in diverse hepatic or serological markers of NAFLD in a total of 13 preclinical studies ( Rosa et al, 2018 ; Shi et al, 2018 ; Wang et al, 2018 ; Chaves Cayuela et al, 2020 ; Ma et al, 2020 ; Tsai et al, 2020 ; Hang et al, 2021 ; Quesada-Vazquez et al, 2021 ; Yang et al, 2021 ; Ding et al, 2022 ; Lee et al, 2022 ; Liggett et al, 2022 ; Yang et al, 2022 ). In addition, we provide comprehensive transcriptomic data by analyzing bulk, single-cell, and spatial transcriptomics to explore the changes in NAC target pathways in liver tissues of mice and patients with NAFLD and to highlight the therapeutic potential of NAC in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…STZ is considered a classic model of diabetes induction because it provokes toxicity to pancreatic β-cells and cellular death [43], resulting in hypoinsulinemia and hyperglycemia. Insulin plays important metabolic role as a suppressor of lipolysis in adipose tissue [44].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Rosa et al, who showed that NAC reduces TG and ALT levels and thus provides low hepatic lipotoxicity. With its antidiabetogenic and antioxidant properties, NAC is beneficial in reducing oxidative stress and diabetic liver damage, which play an important role in the development of diabetes and its complications (Rosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%